ANALISIS PENGARUH MATA KULIAH PENDIDIKAN NILAI DAN KARAKTER ISLAMI TERHADAP ETIKA MAHASISWA TERHADAP ETIKA MAHASISWA PAI SEBAGAI CALON GURU - Febriani, Evi; Faizah, Syiva Rahma; Lingga, Yustita Marsya; Sari, Silvia Nurmutia; Fatimah, Siti; Kumaidi, Muhamad (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
This research discusses the importance of Islamic value and character education in shaping the personality of Islamic Religious Education (PAI) students as prospective teachers with noble character, professionalism, and integrity. This topic was chosen because PAI students have a moral responsibility as agents of change and role models for students and society. The service method used is descriptive-qualitative through conceptual analysis of the application of Islamic values in the campus environment, both in lecture activities and non-formal activities. The results of the study show that Islamic value education plays an important role in shaping honesty, trust, responsibility, tawadhu', and student discipline. The implementation of these values is carried out through habituation, lecturer examples, and campus activities with religious and inclusive nuances. In addition, Islamic character education has also been proven to increase the work readiness of prospective teachers by fostering professional ethics, social empathy, and a balanced personality between intellectual and spiritual aspects. In conclusion, Islamic values and character education is the main foundation in producing prospective PAI educators who are not only academically intelligent, but also have high morals and morals.